ANALISIS KEPEMILIKAN INSTITUSIONAL, RETURN ON EQUITY (ROE), DEBT TO EQUITY RASIO (DER), DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA SAHAM PERUSAHAAN SEKTOR PROPERTI PERIODE TAHUN 2013-2017 - Arrafi, Muhamad Faiz (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This research was conducted to analyze the effect of institutional ownership, profitability, capital structure, and firm size on firm value. The data used in this study were obtained from the financial statements of property and real estate companies listed in the Indonesian Syariah Stock Index (ISSI) in 2013-2017. This study uses panel data analysis. The results of the study show that simultaneously institutional ownership, profitability, capital structure and firm size variables have a positive effect on firm value. While partially institutional ownership and profitability variables have a significant positive effect on firm value. Capital structure has a negative and significant effect on firm value. While the variable size of the company does not affect the value of the company.